ANALYSIS OF THE FIFTH GRADE STUDENTS’ HIGHER ORDER THINKING SKILLS ON SCIENCE IN THE ECOSYSTEM THEME AT ELEMENTARY SCHOOLS - Oktyas Wahyu Kurniawati; Nuriman; Kendid Mahmudi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study is to describe the students’ higher order thinking skills based on the concept of cognitive domain thinking in the revised version of Bloom's taxonomy on the science with ecosystem themes at elementary schools. This study used descriptive research with qualitative approach. The subjects of this study were the fifth grade students at SDN Kepatihan 06 Jember, SDN Sumbersari 03 Jember, and SDN kebonsari 04 Jember. The data were collected through tests and interviews. The results of this research were the students’ higher order thinking skills in the elementary schools had various categories, namely low, medium and high categories. From the results of the study, it can be concluded that the students’ higher order thinking skills on the science with ecosystem theme at elementary schools were low category with 86.08%, medium category with 12.66%, and high category with 1.26%. The low level of thinking ability was influenced by the level of understanding of the concepts in the ecosystem material that led students to have problem in understanding it.